2008
DOI: 10.2209/tdcpublication.49.199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Mouse Tongue Epithelium Focusing on Cell Proliferation Rate and Morphological Aspects

Abstract: The aim of this study was to investigate cell proliferation rate and certain morphological features of mouse epithelium as aging progresses. Tongue biopsies were performed on female mice (Mus domesticus domesticus) at 2, 8, 14 and 20 months of age as indicative of adolescence, adulthood, early senescence and senescence, respectively. Histological sections of tongue were stained with hematoxylin-eosin and subjected to silver staining for active nucleolar organizer region counting. Cell proliferation rate and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…On the other hand, PCNA reaction showed positive immunostaining in the pigeon's tongue. These observations were also recorded by Cameron (1972), Cleaton‐Jones (1976), Leith (1978), Whiteley and Horton (1963), but the absence of the proliferate immunoreactivity was observed by Carrard et al (2008), Çelenligil‐Nazliel, Ayhan, Uzun, and Ruacan (2000) and Hornstein and Schell (1975).…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, PCNA reaction showed positive immunostaining in the pigeon's tongue. These observations were also recorded by Cameron (1972), Cleaton‐Jones (1976), Leith (1978), Whiteley and Horton (1963), but the absence of the proliferate immunoreactivity was observed by Carrard et al (2008), Çelenligil‐Nazliel, Ayhan, Uzun, and Ruacan (2000) and Hornstein and Schell (1975).…”
Section: Discussionsupporting
confidence: 54%
“…Animal studies suggest that the epithelial thickness of the oral mucosa decreases with age, which is accompanied by an increase in the thickness of the keratin layer. The epithelial cell proliferation rate was not altered with age (11).…”
Section: Changes To the Oral Mucosa With Agingmentioning
confidence: 84%
“…The results of these studies indicated that intermediate layer cells are responsible for increased cell proliferation, and no change was observed in basal layer cells in any group since these cells are constantly undergoing physiological division. Therefore, when there is a greater demand for cell replacement, intermediate layer cells, which normally do not proliferate very actively, show increased proliferative activity [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%